Brill's companion to Propertius - Günther, Hans Christian. (Brill's Companions to Classical Studies., 2006)
The present volume provides a comprehensive guide to one of the most difficult authors of classical antiquity. All the major aspects of Propertius' work, its themes, the poetical technique, its sources and models, as well as the history of Propertian scholarship and the vexed problems of textual criticism, are dealt with in contributions by Joan Booth, James Butrica, Francis Cairns, Elaine Fantham, Paolo Fedeli, Adrian Hollis, Peter Knox, Robert Maltby, Tobias Reinhardt and Richard Tarrant; due space is also given to the reception of the author from antiquity and the renaissance (Simona Gavinelli) up to the modern age (Bernhard Zimmermann). At the centre stands an interpretation of the four transmitted books by Gesine Manuwaldt, Hans-Peter Syndikus, John Kevin Newman and Hans-Christian Günther.